2011
DOI: 10.1614/ws-d-10-00063.1
|View full text |Cite
|
Sign up to set email alerts
|

On the Identity of the Weedy Bittercresses (Cardamine : Brassicaceae) in United States Nurseries: Evidence from Molecules and Morphology

Abstract: Bittercress (Brassicaceae) is one of the most prolific and costly weeds of the container nursery industry. Bittercress accessions from container nurseries throughout the major production zones in the United States were examined and compared with herbarium specimens. The identity of these weedy bittercress species were further explored using sequences of the nuclear ribosomal DNA (nrDNA) internal transcribed spacer (ITS) region and the nrDNA region for the COP1-interacting protein 7 (CIP7). Four species of bitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…When not obvious, C. flexuosa and C. hirsuta were identified using morphological keys (Post et al ., 2011). The incidence of backcrossing is seemingly low, if at all possible, as we found none out of a total of 115 plants in the study sites screened for their ploidy level using flow cytometry (CyFlow Space; Sysmex Partec, Goerlitz, Germany; using CyStain UV Precise P reagents, Sysmex Partec).…”
Section: Methodsmentioning
confidence: 99%
“…When not obvious, C. flexuosa and C. hirsuta were identified using morphological keys (Post et al ., 2011). The incidence of backcrossing is seemingly low, if at all possible, as we found none out of a total of 115 plants in the study sites screened for their ploidy level using flow cytometry (CyFlow Space; Sysmex Partec, Goerlitz, Germany; using CyStain UV Precise P reagents, Sysmex Partec).…”
Section: Methodsmentioning
confidence: 99%
“…Cardamine occulta grows in flower beds and pots, at the edges of roads, among cobblestones or paving stones, or on pavements, often in irrigated places. In most cases, it was apparently introduced as a weed, often with mulch, from plant nurseries where it finds appropriate growing conditions (as reported from North America by Post et al 2011). However, the species was also found in rice fields in northern Italy, where it was most likely introduced with rice from Eastern Asia.…”
Section: Resultsmentioning
confidence: 99%
“…Flexuous bittercress (Cardamine flexuosa With. ), one of the most common weeds in container nurseries in the United States (Post et al 2011), has been reported to have populations in European nurseries that are resistant to isoxaben (Eelen and Bulcke 1997). Continuous reliance on the PPO inhibitor herbicides oxyfluorfen, flumioxazin, and oxadiazon for bittercress control also establishes the potential for resistance development.…”
Section: Herbicide Resistance In Container-nursery Production: Potentmentioning
confidence: 99%